(untitled) (LEARNing Landscapes, 2016)
This article presents the English for Speakers of Other Languages (ESOL) Know Your Rights Tool Kit, a popular education resource developed collaboratively by action researchers, ESOL instructors, and undocumented migrant adults. The tool kit draws on migrant learners’ commitments to learning English while facilitating their developing knowledge of human and legal rights literacy information. The article situates resources engaged in ESOL classrooms within a psychopolitical educational framework (Prilleltensky, 2008) and discusses the tool kit’s contributions towards bolstering these resources. It concludes with next steps for the tool kit, focusing upon its potential to foster action and advocacy within migrant communities.